PEMENUHAN HAK – HAK REPRODUKSI NARAPIDANA WANITA DI LAPAS PEREMPUAN KELAS IIB BATAM TAHUN 2018 - Dawinta, Asha; Utami, Risqi (Universitas Batam, 2018)
Reproduction rights are rights that are owned by everyone, to decide freely and responsibly about the number of children, the distance between children, and the determination of the time of birth of a child. In Indonesia, there is no treatment or addition of special rights to female prisoners in prisons. Though women have cycles such as menstruation, pregnancy, childbirth and breastfeeding. The lack of prison capacity, incomplete facilities, plus the lack of wardens are triggers of poor reproductive rights services. The aim of the study was to find out the fulfillment of reproductive rights at correctional institution for women class IIBBatam. This study adopted a qualitative method approach with descriptive design. This research was carried out in April - September 2018 in Women's Prison and Ministry of Justice and Human Rights Regional Office. This study applied purposive sampling technique with a number of 10 respondents. The data was analyzed by reduction, presentation and conclusion. The conclusions of this study from 12 reproductive rights 10 reproductive rights are fulfilled and 2 rights are not fulfilled in the women's quarters of Class IIB Batam with various reasons for obstacles namely inadequate place, budget, infrastructure and health personnel. It is hoped that with the health aspect in development must be taken into consideration, one form of implementation is the government's obligation to provide an adequate budget for health development, including in the Penitentiary.